Development of plasma cutter machine as a teaching support tool in engineering careers (Agroindustria, Sociedad y Ambiente, 2020)
The use of automated equipment such as the plasma cutter reduces manufacturing times, in addition to being more accurate in the cutting of a wide range of metals, the use of this type of device optimizes manufacturing processes in the manufacture of equipment for processing raw materials from the agricultural sector, as well as electromechanical equipment and implements used in the agro-industrial sector. From the academic point of view, the use of this type of machine familiarizes future professionals with new generation equipment and reduces the duration of laboratory practices, which decreases the stress and anxiety conditions of the engineering students, improving their academic performance. Therefore, the objective of this research was to design a prototype plasma cutter, which was used for the practical activities of the electromechanical engineering student, for the evaluation of the efficiency of the prototype, the duration of the academic activities was quantified, as well as the degree of satisfaction of the students in the elaboration of the academic activities. The results found reveal that the practice time was considerably reduced compared to practices carried out under conventional educational approaches, in addition to the fact that the level of stress and anxiety among the students who used the plasma cutter in their practical activities was lower, which positively influenced their academic performance.
Keywords: automation; industrial process efficiency; industrial process